The Dynamics of Intimate Partner Violence and Its Impact on HIV Care: A Cross-Sectional Study of People of Mixed Gender and Sexual Preference in Lima, Peru. Issue 1 (January 2023) - Nelson, Adrianne K.; Denavit, Chloe; Muñoz, Maribel; Wong, Milagros; Saldaña, Olga; Santa Cruz, Janeth; Rodriguez, Carly A.; Caldas, Adolfo; Castro, Arachu; Shin, Sonya
Intimate partner violence (IPV) is associated with a higher risk of contracting HIV and developing worse HIV outcomes. This cross-sectional, mixed methods study presents data on IPV using the Conflicts Tactics Scale (CTS2-S) among 180 persons with HIV in Lima, Peru, as well as qualitative interviews with 7 of them and 18 of their community caregivers. This study used data collected for a randomized controlled trial (RCT), CASAommunity Based Accompaniment with Supervised Antiretrovirals (CASA) Community-based Accompaniment with Supervised Antiretrovirals (CASA). Physical or sexual IPV was self-reported in 82 (45.6%) of participants reporting having been in a relationship in the last year and 59, 8% of those were involved in bidirectional violence. Coping subscales, social support, and stigma were associated with IPV. Intimate partner violence negatively impacted patient adherence to medication and care, particularly during times of severe conflict. In conclusion, profound psychosocial vulnerability—including low social support, substance use as coping, and HIV stigma—contextualize IPV among people with HIV. Bidirectional violence often evolved over time as victims negotiated inter-personal strategies for survival, including retaliation. Interventions should focus on a deeper understanding IPV and facilitating of coping mechanisms to help people with HIV stay in care.